Methane concentration and diffusive flux in the Northern Sea off Heligoland in 2023 - Ingeborg Bussmann; Philipp Fischer (PANGAEA, 2025)
As part of the MOSES Project, in April 2023 methane measurements were started in the north-western part of the island Heligoland in the German Bight (North Sea). The objective was to complement the measurements of the "Sternfahrten" to identify the carbon cycle and its flow from the start of the Elbe river into the North Sea. Therefore, a Contros methane sensor for dissolved methane was deployed under water at about 10 to 12 meter depth (depending on the tide) close to the underwater observatory (UW-OBS) MarGate (54°11 extquotesingle N, 7°52 extquotesingle E), from the COSYNA Project. To ensure correct values latter was cleaned frequently from growing organisms by scientific divers. The present data contains the data from 2023, the first year running the sensors. Based on the concentrations of dissolved methane the methane emissions (diffusive flux) was calculated.